Infâncias em situação de acolhimento - Freitas, Debora Duarte (2012)
With interest added the author s personal concerns as a researcher came study Childhood in host situation that aims to understand how to produce the host institution in Brazil, especially the host Uletus in Rio Grande RS. For this have been selected the theorical field from Michel Foucault, from some methodological tools such as genealogy and discourse. For better development of the research we opted for dismemberment of the dissertation in two articles. The first titled Host institution: one wrapped of law, bodies and disciplines aims to understand how emerged the current home institution in Brazil. The text in question talks over laws and documentation that produced this institutions and thus allows us to understand the times that children become targets of surveillance, classification and incarceration in our country. It is tried to demonstrate too, that the host institutions in their beginning aims to civilizing and disciplining in that children are targets for major objectives achievements. In current days the host measure are a protection to children and adolescents, but in the genesis was designated to protect the social order, which could be threatened by these abandoned minors . The second article, in turn, entitled The production of bodies and the purpose of a host institution in the city of Rio Grande RS try to understand how children bodies have been produced in the host institution Uletus in the city of Rio Grande RS. In this paper we demonstrated the inconsistency of the social discourse of the time with the birth and reality of a shelter in Rio Grande. Interviews were conducted with current employees of the host, as well as with employees who have participated in the genesis of the shelter. Through the sources, were seen and thought of the host institution in our society as mechanisms that have other goals that not only the care of neglected children and adolescents, but as institutions that serve as security mechanisms.